The meaning of the care provided by the nursing staff in the vision of hospitalized elderly in a public hospital - Batista, Virna de Vasconcelos; Fontoura, Elaine Guedes; Rosa, Darci de Oliveira Santa (Revista de Enfermagem UFPE on line, 2011)
ABSTRACT Objective: to get to know the meaning of the care provided by nursing staff in the vision of hospitalized elderly patients at the clinic of a public hospital. Methodology: qualitative research, conducted from January to March of 2009 with ten elders of both sexes hospitalized in the medical clinic at a public hospital in the city of Feira de Santana, Bahia. The data collection instrument was a semi-structured recorded interview. Data analysis was made by the method of thematic content analysis. The study was approved by the Ethical Committee of the Faculdade de Tecnologia e Ciências, resolution no. 0589-2008. Results: two themes emerged from the testimonies: the meaning of care in the vision of elderly and the positive and negative aspects of care received by nursing staff. The elderly have a positive view of care received by nursing staff relating to dedication, love and humanization. Regarding the negative aspects of care received, they relate: lack of communication and information about their health state. Conclusion: because it is a fragile stage of life, elderly people require special attention, sensitive care by the nursing staff. Descriptors: care; elderly; hospital; medical clinic; nursing. RESUMO Objetivo: conhecer o significado do cuidado prestado pela equipe de enfermagem na visão dos idosos internados na clínica médica de um hospital público. Metodologia: pesquisa qualitativa, realizada de janeiro a março de 2009 com dez idosos de ambos os sexos internados na clínica médica de um hospital público da cidade de Feira de Santana, Bahia. O instrumento de coleta de dados foi uma entrevista semi-estruturada, gravada. A análise dos dados foi realizada pelo método de análise de conteúdo temática. O estudo foi aprovado pelo Comitê de Ética da Faculdade de Tecnologia e Ciências pelo parecer nº 0589-2008. Resultados: dos depoimentos emergiram duas categorias temáticas: o significado do cuidado na visão dos idosos e os aspectos positivos e negativos do cuidado recebido pela equipe de enfermagem. Os idosos têm visão positiva do cuidado recebido pela equipe de enfermagem relacionando a dedicação, humanização e amor. Quanto aos aspectos negativos do cuidado recebido referem: falta de comunicação e informações sobre o seu estado de saúde. Conclusão: por se tratar de uma fase de fragilidade da vida a pessoa idosa requer uma atenção especial, um cuidado sensível pela equipe de enfermagem. Descriptores: cuidado; idosos; hospital; clínica médica; enfermagem. RESUMEN Objetivo: conocer el significado del cuidado ofrecido por el equipo de enfermería en la visión de mayores internados en clínica médica de un hospital público. Metodología: investigación cualitativa, realizada de enero a marzo de 2009 con diez mayores de ambos sexos internados en clínica médica de un hospital público de la ciudad de Feira de Santana, Bahia. La recolecta de datos fue através de entrevista semiestructurada y grabada. El análisis de datos fue realizado por el método de análisis de contenido temático. El estudio fue aprobado Comité Ética Facultad de Tecnología y Ciencias con el parecer nº 0589-2008. Resultados: de los testimonios emergieron dos categorias temáticas: significado del cuidado en la visión de los mayores y los aspectos positivos y negativos del cuidado recibido por el equipo de enfermería. Los mayores tienen una visión positiva del cuidado recibido por el equipo de enfermería relacionando dedicación, humanización y amor. Cuanto a los aspectos negativos del mismo refieren: falta de comunicación e informaciones sobre su estado de salud. Conclusión: tratándose de una fase de fragilidad de la vida, la persona mayor requiere una atención especial y cuidado sensible por el equipo de enfermería. Descriptores: cuidado; mayores; hospital; clínica médica; enfermería.